Does unconventional monetary and fiscal policy contribute to the COVID inflation surge in the US? - Jing Cynthia Wu; Yinxi Xie; Ji Zhang (Bank of Canada, 2024)
We assess whether unconventional monetary and fiscal policy implemented in response to the COVID-19 pandemic in the U.S. contribute to the 2021-2023 inflation surge through the lens of several different empirical methodologies-event studies, vector autoregressions, and regional panel regressions using granular data-and establish a null result. The key economic mechanism works through a disinflationary channel in the Phillips curve while monetary and fiscal stimuli put positive pressure on inflation through the usual demand channel. We illustrate this negative supply-side channel both theoretically and empirically.
Keywords: E31; E52; E63; 330; Inflation and prices; Monetary policy; Fiscal policy; Business fluctuations and cycles; Central bank research